A guide to laboratory investigations - McGhee, M. F. (CRC Press, 2014)
With increasing responsibility being placed on primary care, this new edition presents guidelines on specific clinical conditions such as heart failure, management of female infertility, specific lipid monitoring in diabetes and guidance for monitoring renal failure. It also includes suggestions for appropriate laboratory tests in certain clinical situations, for example; dementia screen, screening tests when a patient presents with a neuropathy, and appropriate tests for patients presenting with hypertension, chronic fatigue syndrome, erectile dysfunction, and gynaecomastia--Publisher